The Effect of Achievement-Motivation-Training, Religiosity, and Resilience on Employee Performance - Burhanuddin Burhanuddin (PT Mattawang Mediatama Solution, 2022)
Employee performance is the main thing in the implementation of the process of achieving the goals of a company organization. The performance of a company's employees is influenced by various factors. This study aims to determine the effect of Achievement Motivation Training, Religiosity and Resilience on employee performance. This research is quantitative research with a correlative approach. The population in this study were Regional Office Office Employees in Makassar City with a total sample of 92 employees. The sampling method in this research uses the census method. The data used in this research are primary and secondary data with data collection techniques in the form of observation, questionnaires, documentation, and literature study. The analysis technique is validity and reliability test, classical assumption test and hypothesis test with multiple linear regression method. The results showed that Achievement Motivation Training had no effect on the performance of sub-district office employees in Makassar City, while religiosity and resilience each had a positive and significant effect on employee performance.